Influence of defective virion core proteins on RNA maturation with an avian sarcoma virus. - Harms, E (1977)
The RNA of the avian sarcoma virus B77 temperature-sensitive mutant LA334 was investigated using electrophoretic analysis. The RNA from mutant virus grown at the nonpermissive temperature (42degrees C) showed a heterogeneous peak between 80 and 125S, and another at about 35S. The RNA of the mutant virus grown at the permissive temperature (35 degrees C) behaved like wild-type B77 virus RNA, exhibiting a major peak at 70S. The homology between the various RNA fractions and virus-specific DNA probe was determined, indicating that mutant virus grown at the nonpermissive temperature contains relatively large amounts of nonviral-specific RNA.